BMI and Outcomes of SARS‐CoV‐2 Among US Veterans. Issue 5 (17th March 2021) - Eastment, McKenna C.; Berry, Kristin; Locke, Emily; Green, Pamela; O'Hare, Ann; Crothers, Kristina; Dominitz, Jason A.; Fan, Vincent S.; Shah, Javeed A.; Ioannou, George N.
Abstract : Objective: The purpose of this study is to examine the associations of BMI with testing positive for severe acute respiratory coronavirus 2 (SARS‐CoV‐2) and risk of adverse outcomes in a cohort of Veterans Affairs enrollees. Method: Adjusted relative risks/hazard ratios (HRs) were calculated for the associations between BMI category (underweight, normal weight, overweight, class 1 obesity, class 2 obesity, and class 3 obesity) and testing positive for SARS‐CoV‐2 or experiencing hospitalization, intensive care unit admission, mechanical ventilation, and death among those testing positive. Results: Higher BMI categories were associated with higher risk of a positive SARS‐CoV‐2 test compared with the normal weight category (class 3 obesity adjusted relative risk: 1.34, 95% CI: 1.28‐1.42). Among 25, 952 patients who tested positive for SARS‐CoV‐2, class 3 obesity was associated with higher risk of mechanical ventilation (adjusted HR [aHR]: 1.77, 95% CI: 1.35‐2.32) and mortality (aHR: 1.42, 95% CI: 1.12‐1.78) compared with normal weight individuals. These associations were present primarily in patients younger than 65 and were attenuated or absent in older age groups (interaction P  < 0.05). Conclusion: Veterans Affairs enrollees with higher BMI were more likely to test positive for SARS‐CoV‐2 and were more likely to be mechanically ventilated or die if infected with SARS‐CoV‐2. Higher BMI contributed relatively more to the risk of death in those younger than 65 years of age as compared with other age categories.